1991
DOI: 10.1177/019251391012001003
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Family Background and Early Marital Factors on Marital Disruption

Abstract: Data from the National Survey of Families and Households for 1987-1988 are used to explore methodological and substantive issues concerning marital dissolution in the United States. "The analysis finds that marital disruptions are seriously underreported by males, making the analysis of male marital histories problematic. Also, the potential impact of reconciliations on the estimates of recent marital disruption based on separation is explored; no upward bias is likely to result from the inclusion of separat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
264
3
14

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 362 publications
(294 citation statements)
references
References 22 publications
13
264
3
14
Order By: Relevance
“…We expect cohabitation to affect union instability in Italy in Spain, because this type of union still has a limited spread in these countries (Liefbroer and Dourleijn, 2006), and it was even less spread at the time when the FFS was carried out. We also consider parents union stability: parental separation is likely to lead the offspring to leave home earlier, to enter a union more quickly, to prefer cohabitation to marriage, and eventually to experience more unstable unions (Pope and Mueller 1976;Greenberg and Nay 1982;McLanahan and Bumpass 1988;Bumpass, Martin and Sweet 1991;Amato 1996). Among individual characteristics, we consider age at union formation: we expect that the younger the person is at the time of union formation, the higher the union instability, possibly because the decision to form a union in not thought enough (Morgan and Rindfuss 1985;South and Spitze 1986;Thornton and Rodgers 1987;Martin and Bumpass 1989).…”
Section: Union Dissolution As a Relatively New Phenomenon In Italy Anmentioning
confidence: 99%
“…We expect cohabitation to affect union instability in Italy in Spain, because this type of union still has a limited spread in these countries (Liefbroer and Dourleijn, 2006), and it was even less spread at the time when the FFS was carried out. We also consider parents union stability: parental separation is likely to lead the offspring to leave home earlier, to enter a union more quickly, to prefer cohabitation to marriage, and eventually to experience more unstable unions (Pope and Mueller 1976;Greenberg and Nay 1982;McLanahan and Bumpass 1988;Bumpass, Martin and Sweet 1991;Amato 1996). Among individual characteristics, we consider age at union formation: we expect that the younger the person is at the time of union formation, the higher the union instability, possibly because the decision to form a union in not thought enough (Morgan and Rindfuss 1985;South and Spitze 1986;Thornton and Rodgers 1987;Martin and Bumpass 1989).…”
Section: Union Dissolution As a Relatively New Phenomenon In Italy Anmentioning
confidence: 99%
“…Although they do not limit their study to the effect of religion on divorce, Bumpass, Castro-Martín, and Sweet (1991) find that religious heterogamy reduces marital stability. Lehrer and Chiswick (1993), who focus on the effect of religion, find that with the exception of Mormons and individuals with no religious identification, stability is similar across the various types of homogamous unions, interfaith unions having generally higher rates of dissolution than intrafaith unions.…”
Section: Religionmentioning
confidence: 99%
“…Parental divorce might affect a child's future marital status through different mechanisms, depending on the age at which a child experiences parental divorce. For young children, parental divorce can affect the child's own marital success through actions that increase the likelihood of divorce such as early marriage, cohabitation, and marrying another child of divorce (Bumpass, Martin, & Sweet, 1991;Wolfinger, 2000). For adult children, some research has shown that the child's marital status is affected by observations or experiences of marriage saliency, in which the adult child experiences anxiety, mistrust, and fear about the future success of their own marriages (Duran-Aydintug, 1997).…”
Section: Effects Of Parental Divorcementioning
confidence: 99%